Improving Student Learning Outcomes By Using Problem Based Learning Classroom - Farida Puspitasari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to increase student learning outcomes after applying the PBL (Problem Based Learning) Learning Model in class V SD Negeri 02 Gayamdompo Semester 1 academic year 2021/2022 in learning Theme 3 Healthy food. The research conducted was Classroom Action Research (CAR). A total of two cycles, with the stages of each cycle being planning, implementing, observing and reflecting. Each meeting is carried out pre-test and post-test to determine the progress of students. In cycle I, students who completed after carrying out the post test were 37.5%. In cycle II, students who completed after carrying out the post test were 62.5%. In cycle III, students who complete after carrying out the post test are 95%. These results indicate that the Problem Based Learning learning model can improve student learning outcomes, especially in Class V Science subjects at SDN 02 Gayamdompo.